2017
DOI: 10.3892/ol.2017.7292
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of DNA methylation by human papillomavirus E6 and E7 oncoproteins in cervical cancer (Review)

Abstract: Human papillomaviruses (HPVs) are double stranded circular DNA viruses that infect cutaneous and mucosal epithelial cells. Almost 99% of cervical cancer has a HPV infection. The early oncoproteins E6 and E7 are important in this cellular transformation process. Epigenetic mechanisms have long been known to result in decisive alterations in DNA, leading to alterations in DNA-protein interactions, alterations in chromatin structure and compaction and significant alterations in gene expression. The enzymes respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 118 publications
(106 reference statements)
4
81
1
Order By: Relevance
“…Hr-HPV E7 protein inhibits retinoblastoma protein, thereby promoting the uncontrolled proliferation and malignant transformation of infected cells (8,9). Sustained E7 protein expression is the pathological basis for CIN and cervical cancer (10)(11)(12). Therefore, E7 protein may be a marker for CIN (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Hr-HPV E7 protein inhibits retinoblastoma protein, thereby promoting the uncontrolled proliferation and malignant transformation of infected cells (8,9). Sustained E7 protein expression is the pathological basis for CIN and cervical cancer (10)(11)(12). Therefore, E7 protein may be a marker for CIN (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…E6 and E7 interact with different pathways to activate DNMTs. Proposed pathways for E6 and E7 include (1) indirect mechanism by specificity protein 1 (Sp1) and E2F, respectively, and (2) direct pathway mediated by E7 . Evidence have attributed the antiapoptotic characterizations of HPV to E6 protein .…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…E7 interacts with Rb in RB‐E2F complex, leading to E2F release that forms E2F/DNMT complex and initiates CpG hypermethylation. In direct role, E7 also binds directly to DNMT1 and performs its stimulating effect . Yeungk et al showed that knockdown of HPV‐16 E6 in cervical carcinoma cell lines results in increased level of p53 and downregulation of DNMT1 that suggests that DNMT1 level is repressed by p53 .…”
Section: Human Papilloma Virusmentioning
confidence: 99%
See 2 more Smart Citations